Proposed guidelines for welding procedures to ensure quality welding of creep strength enhanced ferritic (CSEF) materials - Sarwar, M. (Asian Research Publishing Network, 2016)
The creep-strength enhanced ferritic (CSEF) materials are enormously used for noncorrosive high-temperature application with very high strength at elevated temperatures. The use of these materials for steam piping, super-heater headers, boiler tubes, boiler drum and pressure vessels in supercritical power plants, do require special attention and consideration as the cost of repair is normally higher than the original work cost. The aim of this paper is to provide the guidelines for necessary checks and inspections to be carried out to prevent any defect or premature failure of welds. The focus of these guides, supplement to the well-known ASME and EN standards, is the welding of CSEF materials for combined cycle, supercritical and ultra-supercritical power plants. Assessment of base metal and filler materials, prior to start of any activity is vital for a quality weld. The qualifications of welding procedures and welders obligatorily be done according to the welding procedure specification. The welding techniques and associated equipment come in precautionary phase. The welding input parameters require strict control during welding and appropriate preheat and post weld heat treatments mandatorily be carried out, It is noted that if applicable and appropriate checks are carried out, the weld with required properties can be made and premature failure of these sensitive welds can easily be prevented. Â© 2006-2016 Asian Research Publishing Network (ARPN).